International Electronic Reporting Model in Croatian Inland WateiWay Navigation - Bukljaš Skočibušić, Mihaela; Drobac, Tomislav; Sić, Željko (Promet - Traffic&Transportation, 2008)
The development of inland wate!Way traffic of the Republicof Croatia over the recent several years has attracted great attentionfrom experts whose tendencies are oriented to the developmentof strategy and traffic policy in the framework of theEuropean Union countries. The traffic increase on inland wate!Ways of Europe will be reflected on the increase in traffic oninland wate!Ways of the Republic of Croatia. Consequently,over the recent years the need has been recognized to improvethe border crossing mobility, as well as to improve the accessibilityto border areas on inland wate!Ways of the Republic ofCroatia. This paper attempts to briefly present the ERJ model(Electronic Reporting lntemational) in inland navigation,whose implementation will enable exchange of border informationamong authorities, vessels and other participants in inlandnavigation, by applying electronic notification messages in orderto facilitate crossing of international borders and trafficmanagement.